THE PRESENCE OF A LITTERMATE DURING MEASUREMENT OF BLOOD PRESSURE REDUCES THE ACCLIMATIZATION TIME IN CONSCIOUS NAÃVE RATS. - Caszo, Brinnell; Awang, Zanariah; Gnanou, Justin; Singh, Harbindarjeet (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: Familiarizing an animal to the procedure is necessary for accurate measurement of blood pressure (BP). However, this requirement considerably prolongs the procedure, which in some instances could add to spurious results. There is, therefore, a need to establish ways that will help reduce stress and minimize the duration required for BP measurements in conscious animals. This study therefore examined the effect of the presence of a littermate on the duration to achieve the first acceptable blood BP measurement using tail-cuff plethysmography in naÃ¯ve conscious rats. Methods: BP was measured in 12-weeks old, in-house naÃ¯ve male Sprague-Dawley rats, either without prior familiarization and without a littermate or after familiarization for 15 minutes, but without a littermate or after familiarization and with a naÃ¯ve male littermate or without familiarization but with a naÃ¯ve male littermate or without familiarization but with a naÃ¯ve female littermate. Time to the first accepted measurement was recorded. Data were analyzed using one-way ANOVA and post-hoc analysis. Results: The duration to the first acceptable BP measurement in familiarized and naÃ¯ve rats was significantly shorter in the presence of a male littermate (p<0.001), but not with a female littermate when compared with that in naÃ¯ve rats without acclimatization or the presence of a littermate. Conclusion: It appears that the presence of a male littermate when measuring BP in naÃ¯ve male rats significantly decreases the duration required for the measurement of BP. This might improve the efficiency of the procedure and even produce better data. Keywords: Familiarization, Littermate, Tail-cuff rat, Blood pressure.